2008
DOI: 10.1007/s12011-008-8154-3
|View full text |Cite
|
Sign up to set email alerts
|

The Protective and Antidotal Effects of Taurine on Hexavalent Chromium-Induced Oxidative Stress in Mice Liver Tissue

Abstract: Acute exposure to hexavalent chromium [Cr(VI)] compounds can cause hepatotoxicity. Reactive intermediates and free radicals generated during reduction process may be responsible for Cr(VI) toxicity. In this study, the effects of pretreatment or posttreatment of taurine on Cr(VI)-induced oxidative stress and chromium accumulation in liver tissue of Swiss Albino mice were investigated. Single intraperitoneal (ip) potassium dichromate treatment (20 mgCr/kg), as Cr(VI) compound, significantly elevated the level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 65 publications
(92 reference statements)
0
35
0
Order By: Relevance
“…K 2 Cr 2 O 7 i.p. administered leads to liver dysfunction [15,20] since the hepatic portal vein carries Cr(VI) to the liver making it susceptible to the first and persistent exposition [21]. Moreover, Bosgelmez et al [20] revealed that a single intraperitoneal Cr(VI) administration caused a significant chromium accumulation in liver tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…K 2 Cr 2 O 7 i.p. administered leads to liver dysfunction [15,20] since the hepatic portal vein carries Cr(VI) to the liver making it susceptible to the first and persistent exposition [21]. Moreover, Bosgelmez et al [20] revealed that a single intraperitoneal Cr(VI) administration caused a significant chromium accumulation in liver tissue.…”
Section: Discussionmentioning
confidence: 99%
“…administered leads to liver dysfunction [15,20] since the hepatic portal vein carries Cr(VI) to the liver making it susceptible to the first and persistent exposition [21]. Moreover, Bosgelmez et al [20] revealed that a single intraperitoneal Cr(VI) administration caused a significant chromium accumulation in liver tissue. Once Cr(VI) enters the body, it can efficiently penetrate cellular membranes through channels for isoelectric and isostructural anions, such as SO 4 2− and HPO 4 2− [22].…”
Section: Discussionmentioning
confidence: 99%
“…Previous observation in fish (Espe and Holen, 2013;Goto et al, 2001Goto et al, , 2003Takagi et al, 2005) and mammals (Bosgelmez et al, 2008;Nandhini et al, 2002;Pasantes-Morales et al, 1980;Sawosz et al, 2004) identified the liver as a primary importance for taurine metabolism. Although the absence of significant change in AST and ALT activities suggests an absence of liver damage by the end of the present experiment, this is likely due to the short duration of this experiment.…”
Section: Impact On the Liver And General Metabolismmentioning
confidence: 93%
“…Taurine has been linked to a number of health benefits, including tissue repair (Gupta et al, 2006;Kingston et al, 2004;Motawi et al, 2007;Sahin et al, 2011;Seki et al, 2005;Shiny et al, 2005;Takatani et al, 2004;Tong et al, 2006;Zhang et al, 2008;Zhang et al, 2010), alleviation of metal toxicity (Aydogdu et al, 2007;Bosgelmez and Guvendik, 2004;Bosgelmez et al, 2008;Gulyasar et al, 2010;Gurer et al, 2001) and bacterial lipopolysaccharide hepatotoxicity (Kim and Kim, 2002). Many of these actions result from two, cascading mechanisms.…”
Section: Health and Immunitymentioning
confidence: 99%